PENGEMBANGAN MODUL PEMBELAJARAN PAI BERBASIS KURIKULUM 2013 DI KELAS V SD NEGERI 21 BATUBASA, TANAH DATAR (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
The problem in this research was the learning of PAI in SD Negeri 21 Batubasa was teacher’s center and limited of teaching materials. This study aimed at developing the PAI learning module based on the 2013 curriculum on understanding Allah's Messangers, being simple life and Ikhlas were valid, practical, and effective. This research was a development research using 4-D model (definition, design, development and dissemination). Based on the results, the PAI learning module was very valid with an average of 3.65 based on validator assessment. The module was considered very practical with an average 3.92 based on teacher’s ratings and average 3.85 based on student’s ratings. The effectiveness of the module on student's learning motivation was in the active category with the average 94.10 and the student's learning activity in the active category with the average 92. The student’s learning outcomes above the Minimum Standard Criteria with an average 85.50. It can be concluded that the PAI learning module developed was valid, practical, and effective.